Biohydrogen production from carob waste of the Lebanese industry by dark fermentation. Issue 2 (25th January 2022) - Bahry, Hajar; Abdallah, Rawa; Chezeau, Benoit; Pons, Agnès; Taha, Samir; Vial, Christophe
Abstract: The aim of the present work is the study of the feasibility of a solid carob waste valorization from the Lebanese food industry using dark fermentation for a second-generation biohydrogen production. The preliminary experiments conducted in 125-mL glass bottles showed that the most effective initial pH was 6.0 and the highest hydrogen yield was 1.38 mol H2 /mol hexose consumed for sucrose, followed by 1.32 mol H2 /mol hexose consumed for carob waste. However, using 2-L bioreactor with pH control, hydrogen productivity were enhanced using carob waste compared to glucose. Two ways of improving dark fermentation were studied. First, the importance of nitrogen source was demonstrated. The hydrogen yield (1.15 ± 0.05 mol H2 /mol hexose consumed) were clearly lower with the iron medium compared to the complete medium (1.28 ± 0.04 mol H2 /mol hexose consumed). Second a simplified medium including only iron and nitrogen was prepared, and by using this medium an improvement of the hydrogen yield were recorded (1.22 ± 0.03 mol H2 /mol of sugar consumed). Then, particle size reduction from 5.0 to 2.5 mm enhanced the hydrogen yield up to 1.37 mol H2 /mol hexose consumed, and productivity up to 0.089 mol H2 /mol hexose consumed/h.